Classroom Assessment Techniques Implemented by English Teachers at MTs.N 2 Bondowoso - Moch. Imam Machfudi (Fenomena, 2018)
The improvement of students' English achievement remains a crucial challenge in secondary education, particularly in aligning assessment practices with instructional goals. Classroom assessment serves as a key strategy to empower both teachers and students in enhancing learning quality. This study aims to describe the classroom assessment techniques implemented by English teachers at MTs.N 2 Bondowoso. Employing a qualitative research design, the study observed and analyzed authentic assessment practices, including formal and informal techniques, portfolios, projects, and self-assessment. The findings reveal a significant positive change in students' English achievement, with assessment focused predominantly on learning processes rather than solely on outcomes. Teachers utilized varied techniques tailored to student needs, fostering self-reflection, collaboration, and continuous feedback. The study concludes that classroom-based authentic assessment effectively improves learning outcomes and recommends that teachers adopt flexible, ongoing assessment strategies integrated with instruction to support student growth and self-directed learning. Peningkatan prestasi belajar bahasa Inggris siswa masih menjadi isu krusial di pendidikan menengah, terutama dalam menyelaraskan praktik penilaian dengan tujuan pembelajaran. Penilaian kelas merupakan strategi utama untuk memberdayakan guru dan siswa dalam meningkatkan kualitas pembelajaran. Penelitian ini bertujuan mendeskripsikan teknik penilaian kelas yang diimplementasikan guru bahasa Inggris di MTs.N 2 Bondowoso. Dengan desain penelitian kualitatif, penelitian ini mengamati dan menganalisis praktik penilaian otentik, meliputi teknik formal dan informal, portofolio, proyek, serta penilaian diri. Temuan menunjukkan perubahan positif signifikan pada prestasi bahasa Inggris siswa, dengan penilaian berfokus pada proses pembelajaran, bukan hanya hasil. Guru menggunakan berbagai teknik yang disesuaikan dengan kebutuhan siswa, mendorong refleksi diri, kolaborasi, dan umpan balik berkelanjutan. Penelitian menyimpulkan bahwa penilaian kelas otentik efektif meningkatkan hasil belajar dan merekomendasikan guru mengadopsi strategi penilaian fleksibel dan berkelanjutan yang terintegrasi dengan pembelajaran untuk mendukung pertumbuhan siswa dan pembelajaran mandiri.